G597 Audit and re-audit of distractions during prescribing in a paediatric critical care unit. (27th April 2015) - Chan, K; Sadasivam, K; Edmonds, N
Abstract : Context: A 6-beded Paediatric Critical Care Unit (PCCU) at Royal London Hospital (UK) with the involvement of consultants, registrars and pharmacists at PCCU. Problem: A previous audit at PCCU showed that prescribing errors occurred at a frequency of 0.02 per PCCU bed days in 2013, with 3 cases of serious drug dose error, incorrect adjustment for renal impairment and electrolyte replacement error. A dedicated prescribing area was introduced in 2013 but the effectiveness was undetermined. Upon observation of prescribing practice at PCCU, it was noticed that prescribers were distracted frequently, which might be contributory to the increase in prescribing errors. Assessment of problem and analysis of its causes: An audit was designed to observe prescribers and to quantify the distractions. The effectiveness of the prescribing area was measured in terms of its usage frequency, prescribing pattern of PCCU doctors and the nature of distractions during prescribing. PCCU doctors were involved, and it was noted that there was high frequency of distractions during prescribing. Interventions on areas such as information provision, education and training, zero tolerance policy and a re-audit were introduced. Intervention: i. Information Provision Prescribing tools were provided at the prescribing area: - latest British National Formulary - laminated common drug and infusion dosage charts - spare drug and infusion charts - stationery: a calculator and pens ii. Education and Training - Immediate feedback was given to staff - Presentations were given at various staff meetings to raise awareness - Safe prescribing practice was reinforced in induction programmes iii. Zero Tolerance Policy - Prominent signage was displayed signifying that the prescribing area was an undisturbed area iv. Re-audit A re-audit was carried out to assess the effectiveness of the interventions Study design: A 1-week prospective, non-blinded, observational audit was performed. The number and nature of distractions was recorded. Primary outcome was the frequency and nature of prescribing errors, which were identified by pharmacists. Interventions were implemented. A 1-week re-audit was performed to assess the effectiveness of the interventions. Strategy for change: There was communication with the staff to devise feasible interventions, which were strongly supported by consultants and pharmacists at PCCU. The audit results were presented 3 times in different staff meetings to raise awareness and educate staff. Measurement of improvement: A 1-week re-audit was performed to assess the number of distractions and the frequency of prescribing errors. Effects of changes: Pre-intervention audit: There were 12 observable distractions and 8 prescribing mistakes before the interventions in one week. Distractions included ward duties and interruptions from colleagues, nurses and visitors. Post-intervention re-audit: There were 0 observable distraction and 3 prescribing mistakes in the re-audit. The interventions also changed the culture of prescribing practice. Lessons learnt: Constant reinforcement of zero tolerance to prescribing errors and ongoing education were the key for the substantial change in prescribing practice. Modifications at the prescribing area effectively reduced observable distractions and prescribing errors. The audit period was very short since this was the first audit on distractions and acted as a pilot study for future audits. Standardised and ongoing reviews with systematic parameters should be devised to ensure the adherence of prescribing practice and to monitor the frequency of prescribing errors. Message for others: Strong leadership is critical in implementing change and sustainability of system change is important. Education of safe prescribing practice is crucial and the most effective way is to bear patient's safety in mind, be mindful and always check the prescriptions before administering.